2015
DOI: 10.1089/jmf.2014.3315
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of Atherosclerosis by the New Medicinal Mushroom Grifola gargal Singer

Abstract: The beneficial effects of edible mushrooms for improving chronic intractable diseases have been documented. However, the antiatherogenic activity of the new medicinal mushroom Grifola gargal is unknown. Therefore, we evaluated whether Grifola gargal can prevent or delay the progression of atherosclerosis. Atherosclerosis was induced in ApoE lipoprotein-deficient mice by subcutaneous infusion of angiotensin II. Grifola gargal extract (GGE) was prepared and intraperitoneally injected. The weight of heart and ves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 43 publications
0
7
0
1
Order By: Relevance
“…Corner, have records of consumption. However, background information on their chemical composition and bioactive properties is very scarce and restricted to C. hariotii [41,42], G. gargal [43,44,45,46,47,48] and L. nuda [13,15,49,50].…”
Section: Introductionmentioning
confidence: 99%
“…Corner, have records of consumption. However, background information on their chemical composition and bioactive properties is very scarce and restricted to C. hariotii [41,42], G. gargal [43,44,45,46,47,48] and L. nuda [13,15,49,50].…”
Section: Introductionmentioning
confidence: 99%
“…Auspiciously, some treatments showed a considerably higher activity than those that had previously been obtained with G. gargal basidiomes and G. frondosa mycelia. Also Harada et al [6], recently reported the amelioration of atherosclerosis and the enhancement of regulatory T cells in a mouse model using G. gargal extracts of the basidiomes.…”
Section: Commentarymentioning
confidence: 96%
“…Our literature search returned four studies investigating the effects of edible mushrooms on atherosclerosis. The mushroom studies included Grifola gargal Singer (gargal) [181]; portobello and shiitake [182]; erinigi, maitake, and bunashimeji (EMB) [183]; and Agaricus blazei (blazei) [184]. The gargal, EMB, and blazei mushrooms were given to ApoE −/− mice, and the portobello and shiitake were given to LDLR −/− mice.…”
Section: Mushroomsmentioning
confidence: 99%